PESAN, KESADARAN, DAN PERILAKU HEMAT LISTRIK RUMAH TANGGA - Yuliati, Lilik Noor; Nurasrina, Irmayani (Jurnal Ilmu Keluarga dan Konsumen, 2012)
This study aims to analyze correlation between electricity-saving messages, awareness of electricity saving, and electricity saving behavior of households in Cimanggu Park, Bogor City. Contohts numbered 113 households selected by stratified random sampling method base on level of electricity power in the house. Data were collected through interviews. Data were analyzed descriptively and Spearman correlation test. The results showed that the contohts trust the television as the media and government as the reference group in power-saving message. Contohts have the awareness and electricity saving behavior in moderate category. Based on the indicators of primary and secondary power utilization, the majority of contohts have been able to make effective use of electricity. Correlation analysis showed that awareness associated significantly with education and household size. Electricity saving behavior was also associated significantly with the number of source messages, number of messages recalled, household size, income per capita, power, and electricity bills.